Inter-institutional data-driven education research: Consensus values, principles, and recommendations to guide the ethical sharing of administrative education data in the Canadian medical education research context - Grierson, Lawrence; Cavanagh, Alice; Youssef, Alaa; Lee-Krueger, Rachelle; McNeill, Kestrel; Button, Brenton; Kulasegaram, Kulamakan (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2023)
Background: Administrative data are generated when educating, licensing, and regulating future physicians, but these data are rarely used beyond their pre-specified purposes. The capacity necessary for sensitive and responsive oversight that supports the sharing of administrative medical education data across institutions for research purposes needs to be developed.Method: A pan-Canadian consensus-building project was undertaken to develop agreement on the goals, benefits, risks, values, and principles that should underpin inter-institutional data-driven medical education research in Canada. A survey of key literature, consultations with various stakeholders, and five successive knowledge synthesis workshops informed this project. Propositions were developed, driving subsequent discussions until collective agreement was distilled.Results: Consensus coalesced around six key principles: Establishing clear purposes, rationale, and methodology for inter-institutional data-driven research a priori; informed consent from data generators in education systems is non-negotiable; multi-institutional data sharing requires special governance; data governance should be guided by data sovereignty; data use should be guided by an identified set of shared values; and best practices in research data-management should be applied.Conclusion: We recommend establishing a representative governance body, engaging a trusted data facility, and adherence to extant data management policies when sharing administrative medical education data for research purposes in Canada.